The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1103/physrevd.86.014032
|View full text |Cite
|
Sign up to set email alerts
|

Unquenching the gluon propagator with Schwinger-Dyson equations

Abstract: In this article we use the Schwinger-Dyson equations to compute the nonperturbative modifications caused to the infrared finite gluon propagator (in the Landau gauge) by the inclusion of a small number of quark families. Our basic operating assumption is that the main bulk of the effect stems from the "one-loop dressed" quark loop contributing to the full gluon self-energy. This quark loop is then calculated, using as basic ingredients the full quark propagator and quark-gluon vertex; for the quark propagator … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
102
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 74 publications
16
102
0
Order By: Relevance
“…[74,75], combined with lattice studies as that of ref. [7], appear to confirm that the presence of light quarks modifies the ghost and gluon two-point and ghost-gluon three-point Green's functions only slightly at the quantitative level.…”
Section: Lattice Qcd Resultsmentioning
confidence: 99%
“…[74,75], combined with lattice studies as that of ref. [7], appear to confirm that the presence of light quarks modifies the ghost and gluon two-point and ghost-gluon three-point Green's functions only slightly at the quantitative level.…”
Section: Lattice Qcd Resultsmentioning
confidence: 99%
“…Indeed, large-volume lattice simulations [5] and the corresponding SDE analysis [79,80] have explicitly shown that even when dynamical quarks are present (i ) the ghost remains massless, and (ii ) the gluon acquires dynamically a (heavier) mass. As a result, the machinery developed here is directly applicable to the unquenched case, with the minimal modification ∆ …”
Section: Discussionmentioning
confidence: 99%
“…This makes terms automatically more infrared divergent, promoting the screening mass to a correction of the wave-function renormalization [152]. Note that therefore at least all one-loop contributions in the gluon equation contribute equally [38,225].…”
Section: Finite-ghost Behaviormentioning
confidence: 99%